Collaborative Game-play as a Site for Participation and Situated Learning of a Second Language - Piirainen-Marsh, Arja; Tainio, Liisa (Scandinavian journal of educational research, 2009)
This paper addresses additional language learning as rooted in participation in the social activity of collaborative game-play. Building on a social-interactional view of learning, it analyses some of the detailed practices through which players attend to a video game as the material and semiotic structure that shapes play and creates affordances for additional language learning. We describe how players engage with the language resources offered by the game, drawing on the vocabulary, constructions, prosodic features and utterances modelled on game dialogue, in building their own actions during collaborative play. With these resources, the players display their ongoing engagement with the game as well as their competences in recognising, reproducing and creatively reshaping the available linguistic resources in their own activities.